Taxonomic revision of the genus Chaetocnemistoptera Borgmeier (Diptera: Phoridae), with the description of five new species - Ament, Danilo César (Zootaxa, 2014)
The Neotropical genus Chaetocnemistoptera is herein revised. Five new species are described—C. lobata, sp. nov., C. magdalena, sp. nov., C. phaeonota, sp. nov., C. pityropyga, sp. nov., C. trichopoda, sp. nov. The hypopygia of the previously described Chaetocnemistoptera palpalis (Borgmeier) and C. formosa (Borgmeier) are illustrated. The female holotype of Chaetocnemistoptera semifurcata (Borgmeier) could not be associated with any male specimen. A species identification key is provided and comments on the homology of structures and on species relationships are made.